Development of Reading Materials Environment-Based in VII Grade Students of Junior High School (SMPN) 1 Kuala, Indonesia - Abram Thiofilus Sitepu; Mutsyuhito Solin; Arif Rahman (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study aims is to find out the development of reading material by using environment base in Junior High School (SMPN) 1 Kuala. The research study used quantitative method by using sample in VII grade student Data with total 160 students from 5 clasess. The result show  multiple intelligences based writing modules is more effective in improving student learning outcomes, this is indicated by the learning outcomes of students who are taught to use a module developed which is higher by 2460 with an average of 76.75% compared to the average value of students using 2220 textbooks. an average of 69.12%.